Implementation of Kurikulum Merdeka in accounting learning - Raka Prasetya; Surani Erni Morowati; Riska Angraeni; Najwa Ananda Mariana (Universitas Pendidikan Indonesia, 2025)
Kurikulum Merdeka is a new approach in Indonesian education designed to improve the quality of learning through developing students' characters, interests, and talents. This study aims to analyze the implementation of the Kurikulum Merdeka at SMKS Bina Warga Bandung, focusing on challenges, adaptation strategies, and the impact on teachers and students. The research was conducted to understand the effectiveness and constraints of this new curriculum, especially in the context of vocational education, which requires synchronization with the world of work. Qualitative methods were used with direct observation techniques and in-depth interviews to analyze teachers' experiences in implementing the curriculum, changes in teaching strategies, and student responses to new approaches. The results show that implementing the Kurikulum Merdeka provides flexibility in learning despite facing challenges such as understanding new concepts and preparing assessment indicators. This study recommends intensive teacher training, administrative alignment, and collaboration with industry to support the successful implementation of the Kurikulum Merdeka and produce graduates who are competent and ready to face future challenges. Abstrak Kurikulum Merdeka sebagai pendekatan baru dalam pendidikan Indonesia yang dirancang untuk meningkatkan kualitas pembelajaran melalui pengembangan karakter, minat, dan bakat peserta didik. Penelitian ini bertujuan menganalisis implementasi Kurikulum Merdeka di SMKS Bina Warga Bandung, dengan fokus pada tantangan, strategi adaptasi, dan dampaknya terhadap guru serta peserta didik. Penelitian dilakukan untuk memahami efektivitas dan kendala kurikulum baru ini, khususnya dalam konteks pendidikan vokasi yang membutuhkan sinkronisasi dengan dunia kerja. Metode kualitatif digunakan dengan teknik observasi langsung dan wawancara mendalam untuk menganalisis pengalaman guru dalam menerapkan kurikulum, perubahan strategi pengajaran, serta respons peserta didik terhadap pendekatan baru. Hasil penelitian menunjukkan penerapan Kurikulum Merdeka memberikan fleksibilitas dalam pembelajaran meskipun menghadapi tantangan seperti pemahaman konsep baru dan penyusunan indikator penilaian. Studi ini merekomendasikan pelatihan intensif guru, penyelarasan administrasi, dan kolaborasi dengan dunia industri untuk mendukung keberhasilan implementasi Kurikulum Merdeka serta menghasilkan lulusan yang kompeten dan siap menghadapi tantangan masa depan. Kata Kunci: akuntansi; Kurikulum Merdeka; pendidikan vokasi